Short and medium-term effects of foreign acquisitions on manufacturing firms: Evidence from Germany - Holger Görg; Jakob Lehr (Economics Letters, 2024)
This paper, for the first time, investigates the impact of foreign acquisitions on German manufacturing firms using, newly available unique administrative micro data spanning 25 years. Based on an event study design combined with propensity score matching techniques, we find that foreign acquisitions significantly increase labor productivity and average wages in acquired firms. A reduction in employment drives both effects.
Keywords: F23; F61; 330; Foreign direct investment; Foreign acquisitions; Firm behavior; Ex-post evaluation